2019
DOI: 10.32552/2019.actamedica.364
|View full text |Cite
|
Sign up to set email alerts
|

Stoma Complications

Abstract: An improper stoma creation can cause many complications, varying from minor to life-threatening ones. Conversely, a good functioning stoma, at the ideal site improves patient’s quality of life. Most of the stoma complications occur in the early postoperative period and all clinicians must be familiar to these complications. All measures before and during operation must be taken to avoid these complications. Careful follow up after post operative period can help early diagnosis, proper treatment quick recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…This would make sense since majority of the study participants in our study never used stoma bags routinely, yet stoma bags are very important in the prevention of skin complications following stoma placement (16). Also ileostomies contain digestive juices which cause insult to the skin resulting in skin excoriation (21), and it's not surprising that they were the commonest complication seen. Contrary to our ndings, Whelan et al (23) in south Africa, reported that the commonest stoma complication was high output stoma representing 80% of all complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would make sense since majority of the study participants in our study never used stoma bags routinely, yet stoma bags are very important in the prevention of skin complications following stoma placement (16). Also ileostomies contain digestive juices which cause insult to the skin resulting in skin excoriation (21), and it's not surprising that they were the commonest complication seen. Contrary to our ndings, Whelan et al (23) in south Africa, reported that the commonest stoma complication was high output stoma representing 80% of all complications.…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly because in children, the anterior abdominal wall is not fully developed which may create changes in xing the bowel to the fascia. But also cough is a common condition in children which cough increases intra-abdominal pressure that has been associated with these prolapses (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…У післяопераційному періоді у 24 хворих спостерігалися ускладнення після формування стом. У ранньому післяопераційному періоді спостерігались: парастомальний дерматит (17) з ерозуванням (8), парастомальний інфільтрат (3), парастомальний абсцес (1), ретракція стоми (3), відходження стоми від шкіри і її провалювання (3), некроз стоми (1), кровотеча (1), неспроможність кукси (1), абсцес черевної порожнини (1). У пізньому післяопераційному періоді відмічено: лігатурні нориці (7), пролапс стоми (3), стриктура стоми (1), парастомальні грижі (2), гіпергрануляції (6).…”
unclassified
“…Виникнення даних ускладнень залежить від багатьох факторів, починаючи від порушень хірургічної техніки та правил формування стоми, неврахування анатомічної будови передньої черевної стінки до порушень правил догляду за стомою, використання неналежних за розмірами калоприймачів. Це все вимагає ретельного догляду за стомою у післяопераційному періоді, а у випадку появи таких пізніх ускладень, як пролапс, стриктура, ретракція, лігатурні нориці, парастомальна грижа -виконання реконструктивно-відновної операції [6,7,8].…”
unclassified